Anti-VEGF antibody leads to later atypical intravitreous neovascularization and activation of angiogenic pathways in a rat model of retinopathy of prematurity - McCloskey, Manabu; Wang, Haibo; Jiang, Yanchao; Smith, George Wesley; Strange, Jeremy; Hartnett, M Elizabeth (Investigative ophthalmology & visual science, 2013)
Inhibiting VEGF improves adult retino/choroido-vascular diseases, but can lead to recurrent intravitreous neovascularization (IVNV), avascular retina (AVA), and retinal detachment in preterm infants with retinopathy of prematurity (ROP). We sought to understand causes of late-onset IVNV and AVA following anti-VEGF using an ROP model. In the Penn model of ROP, postnatal day (p)12 pups received 1 μL intravitreal VEGFA164 antibody (anti-VEGF; 25-100 ng) or IgG control in each eye. Analyses included lectin-stained percent IVNV and AVA; VEGF protein, erythropoietin, phosphorylated extracellular signal-related kinases and signal transducer and activator of transcription-3 (p-STAT3); and immunohistochemistry of retinal sections for p-VEGFR2. Western blots of human retinal microvascular endothelial cells (hRMVECs) stimulated with VEGF or erythropoietin were analyzed for p-STAT3. Statistical analysis was performed with one-way ANOVA or two-tailed t-tests. At p18, 50 ng anti-VEGF reduced IVNV, and at p25, caused increased IVNV and AVA compared with controls. VEGF and p-VEGFR2 labeling increased following 100 ng anti-VEGF. Following 50 ng anti-VEGF, reduced p-STAT3 and increased erythropoietin occurred at p18. Erythropoietin or VEGF stimulated hRMVEC proliferation and STAT3 activation. In vivo, anti-VEGF reduced pup growth. Increases in erythropoietin and angiogenic signaling following anti-VEGF may account for recurrent IVNV. Anti-VEGF reduced pup growth. Research is needed regarding safety, dose, and type of antiangiogenic treatment for ROP.